ProANP31-67 ameliorates adverse cardiac remodeling and improves systolic and diastolic functions in a preclinical model of cardiorenal syndrome. (10th June 2022) - Silva, GJJ; Parvan, R; Shen, X; Frisk, M; Altara, R; Strand, ME; Rypdal, KB; Lunde, IG; Louch, WE; Aronsen, JM; Stenslokken, K-O; Stokke, MK; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): South-Eastern Norway Regional Health Authority (HSØ-RHF, Project No. 25674) Background: The cardiac hormone proANP31-67, a linear fragment of the N-terminal Atrial Natriuretic Peptide, has known enhancing renal effects. More recently, we described the cardio protective effects of this hormone in a model of chronic hypertension. More specifically, independently of the blood pressure level, proANP31-67 improved diastolic function, attenuated cardiac fibrosis, and reduced hypertrophy. Purpose: The current study was designed to assess the cardiorenal effects of proANP31-67 in a rodent model of hampered renal function, followed by cardiac injury produced by ischemia/reperfusion (I/R). Methods: Right uninephrectomy (UNX) was performed in Wistar rats (n=28). Sixteen weeks after UNX, rats underwent cardiac I/R injury and randomly assigned to proANP31-67 (50 ng/kg/day s.c., n=15) or Vehicle (n=13) for four weeks post I/R. Echocardiographic examinations were performed at baseline (before UNX), 16 weeks after UNX, and four weeks after I/R. At the end of the study, cardiomyocytes were isolated and tissue samples were collected. Results: Chronic UNX resulted in diastolic impairment (E/A: 1.47±0.08 at baseline vs 0.98±0.14 at 16 wks post UNX, p=0.0010). I/R further accentuated the development of the cardiorenal syndrome, and induced a mild systolic dysfunction in the placebo treated animals. However, four weeks of treatment with proANP31-67 preserved systolic function (EF: 62±3% placebo vs 74±2% proANP31-67, p<0.0001), and reverted the diastolic dysfunction (E/A: 0.72±0.15 placebo vs 1.24±0.11 proANP31-67, p=0.0134). ProANP31-67 ameliorated the adverse cardiac remodeling (i.e., reduction in the cardiomyocyte cross-sectional area and interstitial fibrosis), enhanced Ca2+ handling, and improved cardiomyocyte t-tubules´ structural changes compared to vehicle. At the cellular level, in vitro experiments demonstrated the direct effect of proANP31-67 on cardiomyocyte hypertrophy (assessed by [3H]-leucine incorporation) induced by endothelin 1 and angiotensin II. Conclusion: ProANP31-67 has a direct cardiomyocyte protective effect, leading to an improvement in Ca2+ homeostasis and t-tubules´ structures and, prevents the development of systolic and diastolic dysfunction in a pre-clinical model of cardiorenal syndrome.